A Faith-Based Public Speaking Mentoring Model for Strengthening Madrasah Students’ Soft Skills - Abdul Goffar; Wildan Miftahussurur (BAMALA Institute, 2026)
This study reports the implementation of a faith-based public speaking mentoring program conducted at Madrasah Aliyah Darul Huda Pengarang Jambesari Bondowoso as part of a community service initiative. The program aimed to strengthen students’ communicative competence and soft skills through structured mentoring activities. A participatory approach combined theoretical instruction with practical simulations, including Master of Ceremony practice and religious speech presentations. Evaluation was conducted using a pretest–posttest performance comparison focusing on speech organization, vocal clarity, nonverbal communication, and self-confidence. The findings indicate observable improvements across all assessed aspects. Students demonstrated clearer speech structure, stronger vocal projection, improved body language, and increased willingness to speak publicly. The integration of faith-based themes enhanced authenticity and reduced speaking anxiety, contributing to greater engagement and confidence. Beyond technical performance, the program fostered leadership readiness and collaborative participation within the madrasah environment. The results suggest that structured and contextually relevant public speaking mentoring can serve as an effective strategy for soft skill development in Islamic secondary education.